2012
DOI: 10.1016/j.ejvs.2011.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Unselected Percutaneous Access with Large Vessel Closure for Endovascular Aortic Surgery: Experience and Predictors of Technical Success

Abstract: pEVR using the Prostar XL device is effective in the majority of patients. In this study there were benefits in terms of reduced postoperative complications, shorter procedures and decreased lengths of stay. Operator experience is a predictor of technical success for pEVR, irrespective of clinical and morphological characteristics at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 10 publications
1
31
1
Order By: Relevance
“…As overall clinical practice evolved and device/sheath technology has improved with respect to both luminal profile reduction and hydrophilic materials, clinicians have become collectively more aggressive in pursuing minimally invasive access 8, 15, 21 . In our own practice, this has translated into a reduction in the number of iliac conduits, once reported to be required in 20% of TEVAR procedures 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As overall clinical practice evolved and device/sheath technology has improved with respect to both luminal profile reduction and hydrophilic materials, clinicians have become collectively more aggressive in pursuing minimally invasive access 8, 15, 21 . In our own practice, this has translated into a reduction in the number of iliac conduits, once reported to be required in 20% of TEVAR procedures 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Metcalfe et al reported that the success rate of percutaneous aortic endovascular repair in 186 femoral arteries was 95.2% 8 . On univariate analysis, they found that vessel depth, diameter, preoperative renal failure, and operator experience predicted failure of the percutaneous technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Metcalfe et al 25 used a cutoff of 20 supervised deployments of Prostar to define a proficiency level, and 15 cases constituted the request for "license." In the hands of experienced operators, the complication rate was 4e7%, close to earlier reports for either technique.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Operator experience is a strong predictor of technical success for SMCD, 3 and excellent results have been reported for experienced operators. 4 In the present study, experience of 15 cases was used to define the basic level, and of 60 procedures the experienced level.…”
mentioning
confidence: 94%